New insights into the mechanisms of lipid-body biogenesis in plants and other organisms. (December 2000) - Murphy, D.J.; Hernendez-Pinzon, I.; Patel, K.; Hope, R. G.; McLauchlan, J.
Abstract : A comparative approach has been used to study the role of several lipid-body-binding proteins in plants and animals. Caleosins are a newly discovered class of calcium-binding lipid-body proteins found in plants and fungi, which we now report to have separate endoplasmic reticulum and lipid-body-associated isoforms. We also compare the lipid-body targeting of oleosin from plants and the core protein of the hepatitis C virus when they were expressed separately in lipid-accumulating animal cell lines. This is a novel and powerful approach to investigating the factors that determine the lipid-body targeting of a wide range of proteins.